RsmV, a Small Noncoding Regulatory RNA in Pseudomonas aeruginosa That Sequesters RsmA and RsmF from Target mRNAs - Janssen, Kayley H. (J Bacteriol, 2018)
The Gram-negative opportunistic pathogen Pseudomonas aeruginosa has distinct genetic programs that favor either acute or chronic virulence gene expression. Acute virulence is associated with twitching and swimming motility, expression of a type III secretion system (T3SS), and the absence of alginate, Psl, or Pel polysaccharide production. Traits associated with chronic infection include growth as a biofilm, reduced motility, and expression of a type VI secretion system (T6SS). The Rsm posttranscriptional regulatory system plays important roles in the inverse control of phenotypes associated with acute and chronic virulence. RsmA and RsmF are RNA-binding proteins that interact with target mRNAs to control gene expression at the posttranscriptional level. Previous work found that RsmA activity is controlled by at least three small, noncoding regulatory RNAs (RsmW, RsmY, and RsmZ). In this study, we took an in silico approach to identify additional small RNAs (sRNAs) that might function in the sequestration of RsmA and/or RsmF (RsmA/RsmF) and identified RsmV, a 192-nucleotide (nt) transcript with four predicted RsmA/RsmF consensus binding sites. RsmV is capable of sequestering RsmA and RsmF in vivo to activate translation of tssA1, a component of the T6SS, and to inhibit T3SS gene expression. Each of the predicted RsmA/RsmF consensus binding sites contributes to RsmV activity. Electrophoretic mobility shifts assays show that RsmF binds RsmV with >10-fold higher affinity than RsmY and RsmZ. Gene expression studies revealed that the temporal expression pattern of RsmV differs from those of RsmW, RsmY, and RsmZ. These findings suggest that each sRNA may play a distinct role in controlling RsmA and RsmF activity. IMPORTANCE The members of the CsrA/RsmA family of RNA-binding proteins play important roles in posttranscriptional control of gene expression. The activity of CsrA/RsmA proteins is controlled by small noncoding RNAs that function as decoys to sequester CsrA/RsmA from target mRNAs. Pseudomonas aeruginosa has two CsrA family proteins (RsmA and RsmF) and at least four sequestering sRNAs (RsmV [identified in this study], RsmW, RsmY, and RsmZ) that control RsmA/RsmF activity. RsmY and RsmZ are the primary sRNAs that sequester RsmA/RsmF, and RsmV and RsmW appear to play smaller roles. Differences in the temporal and absolute expression levels of the sRNAs and in their binding affinities for RsmA/RsmF may provide a mechanism of fine-tuning the output of the Rsm system in response to environmental cues.